Review of 30 pulmonary hamartoma cases: Follow-up and treatment - Sezer, Hüseyin Fatih; Elicora, Aykut; Abdullayev, Galbinur; Topçu, Salih (Journal of Surgery and Medicine, 2021)
Background/Aim: The most common benign tumor of the lung is hamartoma. Lung hamartomas are tumors of benign mesenchymal origin with intraparenchymal or endobronchial localization. They are more common in the 40-60-years age range and among males. It is important to distinguish hamartomas from malignancies due to their radiological appearance. The main treatment is surgical excision. They tend to grow slowly, and malignant transformation is rare. Therefore, the decision of resection or follow-up and timing of the surgical intervention are important. In our study, we aimed to present our follow-up and treatment results and recommendations of 19 years of pulmonary hamartoma experiences. Methods: In this case series, the data of 30 patients with hamartomas as diagnosed by histopathological examination, who underwent surgical resection, bronchoscopy, and transthoracic lung biopsy between January 2001 and May 2020 were analyzed retrospectively. Radiologic and nuclear medicine imaging features, which are clinically important, were divided into groups and compared. Results: The mass was removed in 12 (40%) patients by enucleation, in 5 (16.7%) patients, by wedge resection, in 3 (10%) patients, by bronchoscopy, and in 1 (3.3%) patient, by bronchotomy, segmentectomy and lobectomy. Seven (23.3%) patients were diagnosed with tru-cut biopsy and did not undergo total mass excision. Trans-thoracic fine needle biopsy (TTFNB) was performed in 7 (23.3%) patients and histopathological diagnosis could not be obtained in any of these biopsies. Concomitant with hamartomas, lung squamous cell carcinoma, lung malignancy in the contralateral lung, prostate carcinoma, and leiomyoma were found in one patient (3.3%) each. Conclusion: Because of their slow growth and rare malignant transformation, lung hamartomas should be diagnosed with less invasive methods. The patients should be followed carefully unless they are symptomatic.